Implementing a Pancasila-Based Content Creator Project in Science Learning to Strengthen Youth Character in Support of the Sustainable Development Goals - Eni Supriati; Encep Syarief Nurdin; Yadi Ruyadi; Tri Suhartati (Postgraduate, University of Mataram, 2026)
This research aims to develop a character development model for youth through a Pancasila content creator project to enhance the understanding and actualization of Pancasila values. This study uses a mixed methods approach, namely qualitative and quantitative, with stages of analysis, exploration, and development of a character development model focused on Pancasila values. The results indicate that the Pancasila Content Creator Project is an effective and innovative character development model that successfully bridges the gap between students’ normative understanding and the practical actualization of Pancasila values. By integrating project-based digital content creation within science learning, particularly through sustainability and anti-bullying themes, the model enables students to internalize Pancasila values across cognitive, affective, and behavioral domains. The high effectiveness scores achieved in both implementation stages (91.72% in PIP 1 and 92.34% in PIP 2) indicate strong impacts on learning processes, participation, understanding, attitudes, behavior, and commitment to Pancasila values, with improvements observed following reflective refinement of the model. However, several obstacles still arise, particularly a digital skills gap, suboptimal teacher coordination, time constraints, and varying levels of home environment support.